PENINGKATAN KREATIVITAS MENGGAMBAR MELALUI POLA BENTUK (SHAPE) - Hidayati, Nurul; Permata, Rista Dwi (FKIP Unirow Tuban, 2020)
Based on the report of study and survey results, there were still problems that were found when drawing activities, including the process of children learning to draw freely given, so students had difficulty drawing according to the object. Many methods or techniques that can be practiced by the teacher motivate students to increase their creativity to make images into a form of image similar to the object.The method that is suitable for researchers to use is class action research or class action research entitled